Diversity codes for differential phase modulation in a correlated Rayleigh fading channel. - Char-Dir Chung (IEEE Transactions on communications)
This paper proposes a simple diversity scheme that makes use of nonlinear block coding, symbol interleaving, and differential phase modulation. The resultant signaling mechanism merits intrinsic time diversity within each codeword, which is resistant to correlated fading. The maximum-likelihood noncoherent receiver which operates over correlated Rayleigh fading is developed. Exact and approximate upper bounds are derived to assess the codeword-error probability characteristics of the proposed system